ANALISIS EKSPLORASI LITERASI KEUANGAN PADA MAHASISWA - Arifin (Jurnal Mahkota Bisnis (Makbis), 2024)
Finding out how important financial literacy instruction is for college students is the aim of this study. Research methodology involves the use of libraries. It is clear from the conversation that in order for students to handle their personal finances, financial literacy is essential. A young person's experience in college is unlike any other. They will embark on a new chapter in their lives once they graduate from college. Soon after graduation, personal financial resources will influence a key decision. Students' firsthand financial management experiences will positively impact their financial literacy. Financial management information is helpful in resolving issues related to budgeting, investments, debt management, saving, and consumption choices. Making financial decisions will depend on one's degree of financial literacy. Making financial decisions will depend on one's degree of financial literacy. It also involves making decisions about financial objectives and emergency fund management. Good money management has an impact on one's personal life